PENGARUH PINJAMAN MODAL TERHADAP PENDAPATAN IBU RUMAH TANGGA JORONG LABUH LURUS NAGARI AIA GADANG BARAT KECAMATAN PASAMANKABUPATEN PASAMAN BARAT(STUDI KASUS : ANGGGOTA PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) - Nadiatul Khaira Ismail; Amsah Hendri Doni (Adisam Publisher, 2025)
This research was motivated by Nagari Aia Gadang Barat, Pasaman District, West Pasaman Regency, which is a Nagari whose residents make their living as farmers, farm laborers and palm oil workers whose income is quite low. The majority of housewives take part in capital loans from PNPM to help their husbands increase their income to meet their family's needs. However, there are still many members of the National Community Empowerment Program (PNPM) community who do not use capital loans provided by PNPM to carry out productive businesses but rather to meet consumer needs, and members who have started doing business do not use these capital loans to develop their business but instead use them to other consumer needs. Finding out how much of an impact capital loans have on housewives' incomes in Nagari Aia Gadang Barat, Pasaman District, West Pasaman Regency is the driving force for this study. The research approach employed here is quantitative, and it makes use of a Likert scale questionnaire as its research instrument. A saturated sample of 40 respondents was used for this research. The research in this area makes use of a variety of tests for analysis, including those for instruments (validity and reliability tests), for traditional assumptions (normality and autocorrelation tests), and for simple linear regression analysis (t-test, coefficient of determination, etc.). Researchers in Nagari Aia Gadang, Pasaman District, West Pasaman Regency, used SPSS 25 to compile their findings. The t-test revealed that the effect of capital loans on housewives' income was statistically significant (t count = 3.166 > t table = 2.024), thus accepting Ha. Housewives' incomes tend to rise in direct proportion to the amount of capital loans they take out. Similarly, housewives' income drops as they take out fewer capital loans.